Asymmetric Copper-Catalyzed C(sp)–H Bond Insertion of Carbenoids Derived from N-Tosylhydrazones - Osako, Takao; Nagaosa, Makoto; Hamasaka, Go; Uozumi, Yasuhiro (Synlett, 2018)
A chiral copper(I)–phosphoramidite complex efficiently catalyzed the asymmetric insertion of the carbenoids derived from N-tosyl hydrazones into alkyne C–H bonds to give the corresponding chiral alkynylated products in up to 77% yield and with up to 74% ee.
Keywords: copper catalysis; asymmetric catalysis; carbenoids; hydrazones; alkynes